In vitro study: HIF-1α-dependent glycolysis enhances NETosis in hypoxic conditions - Ye, Yi; Wang, Yanjun; Xu, Qiying; Liu, Juanli; Yang, Ziqi; Wuren, Tana; Ge, Ri-Li (Frontiers in Immunology, 2025)
BackgroundHypoxia plays a pivotal role in modulating immune responses, especially in neutrophils, which are essential components of the innate immune system. Hypoxia-inducible factor (HIF)-1α, a key transcription factor in hypoxic adaptation, regulates cellular metabolism and inflammatory responses. However, the impact of HIF-1α-dependent glycolysis on the formation of neutrophil extracellular traps (known as NETosis) under hypoxic conditions remains unclear.MethodsWe employed two established neutrophil models, neutrophils isolated from human whole blood and DMSO-induced dHL-60 cells, to explore the role of HIF-1α in regulating glycolysis and its influence on NETosis under hypoxic conditions. We utilized western blotting, immunofluorescence staining, ELISA, and flow cytometry to evaluate the expression of key glycolytic enzymes and NETosis markers under hypoxia. Additionally, the effects of inhibiting HIF-1α with LW6 and blocking the glycolytic pathway with Bay-876 were investigated.ResultsHIF-1α-dependent glycolysis, through the upregulation of key glycolytic enzymes, significantly enhances NETosis under hypoxic conditions. Pharmacological inhibition of HIF-1α with LW6 and glycolytic blockade with Bay-876 markedly reduced NETosis, underscoring the crucial role of metabolic reprogramming in neutrophil function during hypoxia.ConclusionThis study provides novel insights into the interplay between metabolic reprogramming and NETosis in response to hypoxic stress. We identify HIF-1α-dependent glycolysis as a key driver of NETs formation, advancing our understanding of the mechanisms underlying hypoxia-related inflammatory diseases. These findings also suggest that targeting metabolic pathways may offer potential therapeutic strategies for modulating immune responses in hypoxia-associated disorders.